2016
DOI: 10.1108/ejtd-07-2015-0057
|View full text |Cite
|
Sign up to set email alerts
|

Regression discontinuity design: a guide for strengthening causal inference in HRD

Abstract: Purpose Regression discontinuity (RD) design is a sophisticated quasi-experimental approach used for inferring causal relationships and estimating treatment effects. This paper aims to educate human resource development (HRD) researchers and practitioners on the implementation of RD design as an ethical alternative for making causal claims about training interventions. Design/methodology/approach To demonstrate the key features of RD designs, a simulated data set was generated from actual pre-test and post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This outcome aligns with typical findings in HRD literature, which questions the efficacy of employee training. In addition, an array of literature questions whether simply making training available truly supports organizational learning (Chambers, 2016; Kreismann & Talaulicar, 2021; Lancaster & Milia, 2014). However, despite an initial failed attempt to affect the perception through intensive exploration of social issues, we reimagined our course, which ultimately showed an effect on 58% (14 of 24) of the learners’ perceptions of the importance of social issues.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome aligns with typical findings in HRD literature, which questions the efficacy of employee training. In addition, an array of literature questions whether simply making training available truly supports organizational learning (Chambers, 2016; Kreismann & Talaulicar, 2021; Lancaster & Milia, 2014). However, despite an initial failed attempt to affect the perception through intensive exploration of social issues, we reimagined our course, which ultimately showed an effect on 58% (14 of 24) of the learners’ perceptions of the importance of social issues.…”
Section: Discussionmentioning
confidence: 99%
“…If the slopes of the regression lines differ (interaction effect) the researcher can also simply calculate the differences of intercepts but needs to shift the assignment variable by the cut-off value to zero (x-c). Another possibility would be to conduct a simple t-test on the groups within the bandwidth b around the cut-off value [c-b; c+b], but the treatment effect then might be underestimated [3,7,16].…”
Section: The Designmentioning
confidence: 99%
“…Since the assignment variable can be any continuous measure, many possible uses of the RDD in medicine or health service research are imaginable. For example, Maciejewski & Basu [16] mentioned the use of the RDD in conjunction with the neonatal intensive care unit (NICU). New-borns underweight (<1500g) more often need intensive care then heavier infants.…”
Section: The Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third paper, "Regression Discontinuity Design: A Guide for Strengthening Causal Inference in HRD", Chambers (2016) reviewed studies in a broad set of HRD-related journals and found that regression discontinuity (RD) has been used very infrequently. Chambers demonstrated the features of RD using a simulated dataset generated from published descriptive statistics.…”
Section: Content Of the Special Issuementioning
confidence: 99%